Salubrinal Exposes Anticancer Properties in Inflammatory Breast Cancer Cells by Manipulating the Endoplasmic Reticulum Stress Pathway - Alsterda, Andrew; Asha, Kumari; Powrozek, Olivia; Repak, Miroslava; Goswami, Sudeshna; Dunn, Alexandra M.; Memmel, Heidi C.; Sharma-Walia, Neelam (Frontiers in Oncology, 2021)
The endoplasmic reticulum (ER) regulates protein folding, post-translational modifications, lipid synthesis, and calcium signaling to attenuate the accumulation of misfolded proteins causing ER stress and maintains cellular homeostasis. The tumor microenvironment is rich in soluble cytokines, chemokines, growth, and angiogenic factors and can drive the ER's abnormal functioning in healthy cells. Cancer cells adapt well to the tumor microenvironment induced ER stress. We identified that the inflammatory breast cancer (IBC) abundantly expresses osteoprotegerin (OPG) and their tumor microenvironment is rich in OPG protein. OPG is a soluble decoy receptor for receptor activator of nuclear factor-kappa B ligand (RANKL), also called osteoclast differentiation factor/osteoclastogenesis inhibitory factor (OCIF). Employing mass spectrometry analysis, we identified a set of ER chaperones associated with OPG in IBC cell lysates (SUM149PT, SUM1315MO2) compared to healthy human mammary epithelial cells (HMEC). Proximity ligation assay (PLA) and immunoprecipitation assay validated the interaction between OPG and ER chaperone and master regulator of unfolded protein response (UPR) GRP78/BiP (glucose-regulated protein/Binding immunoglobulin protein). We detected remarkably high expression of CCAAT enhancer-binding protein homologous protein (CHOP), inositol-requiring enzyme 1 (IRE1α), protein disulfide-isomerase (PDI), PKR-like ER kinase (PERK), activating transcription factor 4 (ATF4), X-box binding protein 1 (XBP-1) and growth arrest and DNA damage-inducible protein (GADD34) in SUM149PT and SUM190PT cells when compared to HMEC. Similarly, tissue sections of human IBC expressed high levels of ER stress proteins. We evaluated cell death and apoptosis upon Salubrinal and phenylbutyrate treatment in healthy and IBC cells by caspase-3 activity and cleaved poly (ADP-ribose) polymerase (PARP) protein assay. We quantitated the OPG secretion from Salubrinal and phenylbutyrate treated healthy and IBC cells by enzyme-linked immunosorbent assay (ELISA). IBC cells were chemosensitive to Salubrinal treatment, possibly via inhibition in OPG secretion, upregulating ER oxidoreductase 1 (ERO1α) protein level, inducing gene expression of ATF4, followed by subsequent upregulation of CHOP, thus ultimately driving caspase-3 mediated IBC cell death. Our findings implicate that manipulating ER stress with Salubrinal may provide a safer and tailored strategy to target the growth of inflammatory and aggressive forms of breast cancer.